Paul Preciado's Uterine Politics: Abolish the Family or Reclaim Confiscated Queer Genetic Patrimony?. Issue 1 (March 2023) - Lewis, Sophie
Abstract : This discussion takes up the politics of gestational labour and uterine productivity in connection with genetic self-reproduction and the family in the oeuvre of Paul B. Preciado. In his autotheoretical treatise Testo Junkie, Preciado dispensed with the standard Marxist-feminist term 'sexual division of labour', positing instead a 'technogestational division of labour' to describe the mechanism by which capitalism segments people's bodies and constructs the capacity to make babies. Taking up that coinage, with enthusiasm for the political horizon it illuminates, I nevertheless read Preciado against Preciado. I identify moments (including in An Apartment on Uranus ) of oscillation away from the earlier work's posit of always already non-sovereign 'politically assisted procreation'; moments which break faith with the 'copyleft' spirit of collective gestational anti-authorship insofar as they call for trans and queer individuals' equal access to 'genetic speech' and for our reappropriation of parental property rights qua 'confiscated patrimony'.